Emerging Ideas. How Do Low‐Income Mothers Talk to Children About Weight and Body Shape?. Issue 5 (14th May 2021) - Bauer, Katherine W.; Branch, Jacqueline M.; Appugliese, Danielle P.; Pesch, Megan H.; Miller, Alison L.; Lumeng, Julie C.; Kaciroti, Niko
Abstract : Objective: Identify mothers' perceptions of how they talk about weight and body shape with their children and examine how approaches vary by mother and child characteristics. Background: Youth who report that their parents talk with them about their weight experience poor health. However, very little is known about the content of these conversations. Method: Mothers and their 6‐ to 11‐year‐old children ( N  = 188 dyads) participated in a mixed‐methods study. Themes in mothers' responses to the interview question "How do you talk to your child about weight or body shape?" were identified, and latent class analysis was used to characterize patterns of weight and shape talk. Results: Seven themes of weight and shape talk were identified, including talking about "Healthy Habits" (39.9%), "Avoids Weight and Body Talk" (21.8%), and tells "Cautionary Tales" (18.6%). Three patterns emerged from themes: talk to promote health, avoid talking about weight and shape, and talk to build children's self‐esteem. Mothers of children with obesity were more likely to talk to promote health versus other patterns. Conclusion: The content of family conversations about weight and shape is diverse. Implications for Emerging Ideas: Future research is needed to understand the impacts of specific ways parents talk about weight and shape.